2012
DOI: 10.1159/000336376
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Restores Pulsatile LH Secretion in Patients with Neurokinin B Signaling Deficiencies: Physiological, Pathophysiological and Therapeutic Implications

Abstract: Pulsatile gonadotropin-releasing hormone (GnRH) is crucial to normal reproductive function and abnormalities in pulse frequency give rise to reproductive dysfunction. Kisspeptin and neurokinin B (NKB), neuropeptides secreted by the same neuronal population in the ventral hypothalamus, have emerged recently as critical central regulators of GnRH and thus gonadotropin secretion. Patients with mutations resulting in loss of signaling by either of these neuroendocrine peptides fail to advance through puberty but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
109
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 59 publications
22
109
1
3
Order By: Relevance
“…However, a male individual with reversible CHH exhibited a robust response to exogenous kisspeptin 145 and continuous kisspeptin infusion was demonstrated to overcome genetic defects in the kisspeptin signalling pathway. 146 In terms of clinical application, kiss peptin has been used with therapeutic effect in women with hypothalamic amenorrhoea, 147 as well as for egg maturation during assisted fertility. 148 Thus, although still investigational, kisspeptin seems to be emerging as useful in several therapeutic areas.…”
Section: Clinical Biochemical and Imaging Investigationsmentioning
confidence: 99%
“…However, a male individual with reversible CHH exhibited a robust response to exogenous kisspeptin 145 and continuous kisspeptin infusion was demonstrated to overcome genetic defects in the kisspeptin signalling pathway. 146 In terms of clinical application, kiss peptin has been used with therapeutic effect in women with hypothalamic amenorrhoea, 147 as well as for egg maturation during assisted fertility. 148 Thus, although still investigational, kisspeptin seems to be emerging as useful in several therapeutic areas.…”
Section: Clinical Biochemical and Imaging Investigationsmentioning
confidence: 99%
“…Pharmacological evidence revealed that injection of kisspeptin-10 and kisspeptin-54 in humans increased gonadotrophin pulsatile release, especially LH [57,58]. The increase in pulsatile secretion of LH by kisspeptins has also been shown in human disease models [59][60][61] has been suggested that kisspeptins also help in adjusting the hypothalamic clock of GnRH pulsatile release in addition to its stimulation in men [62], but the evidence does not support this effect in women [63]. The reason suggested for this was differential sex steroid feedback in females due to changes in hormonal levels across the menstrual cycle and sexual dimorphism in functional neuroanatomy of kisspeptins [1].…”
Section: The Role Of Kisspeptins In Gnrh Pulse Generationmentioning
confidence: 96%
“…В то время как триггеры самопроизвольного купирования гипогонадизма остаются мало-изученными, эти клинические наблюдения, очевидно, представляют важные ориентиры и относительно физиологической иерархии, и относительного влияния нейрокинина B и кисспептина на модуляцию выброса ГнРГ. Вероятность того, что действие нейрокинина B содружественно действию кисспептина, под-тверждается наблюдением повышения частоты повторения импульсов ЛГ во время инфузии кисспептина у женщин с недостаточностью В-нейрокининовой сигнализации [96].…”
Section: мутации в генах нейрокининовых сигнальных путейunclassified